2020
DOI: 10.1055/a-1264-7511
|View full text |Cite
|
Sign up to set email alerts
|

EUS-guided intrahepatic biliary drainage: a large retrospective series and subgroup comparison between percutaneous drainage in hilar stenoses or postsurgical anatomy

Abstract: Background and study aims Endoscopic ultrasound-guided intrahepatic biliary drainage (EUS-IBD) struggles to find a place in management algorithms, especially compared to percutaneous drainage (PTBD). In the setting of hilar stenoses or postsurgical anatomy data are even more limited. Patients and methods All consecutive EUS-IBDs performed in our tertiary referral center between 2012 – 2019 were retrospectively evaluated. Rendez-vous (RVs), antegrade stenting (AS) and hepatico-gastrostomies (HGs) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
47
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 38 publications
(41 reference statements)
0
47
0
1
Order By: Relevance
“…In malignant distal biliary obstruction, all options including EUS-RV procedures, EUS-CDS, EUS-HGS, EUS-guided antegrade stent placement, and EUS-GBD may be considered, whilst in malignant hilar obstruction only EUS-guided antegrade stent placement and EUS-HGS are feasible alternatives. EUS-HGS can be complementary to ERCP in patients with an unresectable hilar stricture and inadequate drainage of the left hepatic duct [23,33,66,67]. Similarly, EUS-guided hepaticoduodenostomy may aid in drainage of the right biliary system [68,69].…”
Section: Key Question 3: What Are the Indications For Eus-bd?mentioning
confidence: 99%
“…In malignant distal biliary obstruction, all options including EUS-RV procedures, EUS-CDS, EUS-HGS, EUS-guided antegrade stent placement, and EUS-GBD may be considered, whilst in malignant hilar obstruction only EUS-guided antegrade stent placement and EUS-HGS are feasible alternatives. EUS-HGS can be complementary to ERCP in patients with an unresectable hilar stricture and inadequate drainage of the left hepatic duct [23,33,66,67]. Similarly, EUS-guided hepaticoduodenostomy may aid in drainage of the right biliary system [68,69].…”
Section: Key Question 3: What Are the Indications For Eus-bd?mentioning
confidence: 99%
“…Recently, we assessed the use of EUS-guided biliary drainage in the context of failed ERCP and postsurgical anatomy. 4 This series included 9 patients in whom a double EUS bypass was performed. Analysis of these procedures revealed that in 6 of 9 combined procedures, significant contrast extravasation or free air surrounding the stomach was seen after successful intrahepatic biliary drainage, 4 which may compromise visualization during EUS-GJ.…”
mentioning
confidence: 99%
“… 4 This series included 9 patients in whom a double EUS bypass was performed. Analysis of these procedures revealed that in 6 of 9 combined procedures, significant contrast extravasation or free air surrounding the stomach was seen after successful intrahepatic biliary drainage, 4 which may compromise visualization during EUS-GJ. Furthermore, in situations where biliary drainage has been performed first, additional insufflation of CO 2 during EUS endoscope insertion or while placing a nasojejunal catheter in preparation for EUS-GJ will keep the transgastric tract patent.…”
mentioning
confidence: 99%
“…The development of linear sectorial array EUS scopes in the early 1990 brought a new approach to the diagnostic and therapeutic dimensions of EUS capabilities, opening the possibility to perform puncture over a direct ultrasonographic guidance. Therapeutic EUS (TEUS) encompasses different procedures such as EUS-guided biliary drainage,[ 1 2 ] drainage of pancreatic fluid collections,[ 3 4 ] pancreatic duct drainage,[ 5 ] gallbladder drainage,[ 6 ] EUS-guided gastroenterostomy,[ 7 8 ] EUS-guided pancreatic tumor ablation. [ 9 ]…”
mentioning
confidence: 99%